Incidence Profile of Side Effects of Anti-Tuberculosis Drugs and Adherence To Taking Medication In Tuberculosis Patients At The Sukolilo 1 Health Center - Putri Regina Lisa Andrayani; Ria Etikasari; Ulviana Yulia Husna (International Journal of Health and Pharmaceutical (IJHP), 2026)
Tuberculosis (TB) is a disease caused by infection with the bacterium Mycobacterium tuberculosis and can be fatal. Long-term TB treatment has the potential to cause side effects, but adherence to medication is still necessary to achieve therapeutic effectiveness, reduce the risk of transmission, and prevent drug resistance. This study aims to determine the relationship between the side effects of anti-TB drugs (OAT) and medication adherence in TB patients at the Sukolilo Community Health Center in Pati. This study used a descriptive observational method with a cross-sectional approach. A total of 100 patients met the inclusion criteria: aged 18–65 years, making outpatient visits during August 2025, having at least two visits with a TB diagnosis, and willing to be research subjects. Respondents with incomplete questionnaires were excluded from this study. The study showed that the majority of patients were aged 61–65 years, male (64.0%), with the highest level of education being elementary school (48.0%), and working as farmers (60.0%). Most patients were married (87.0%) and had a family of four (40.0%). The most common side effect of OAT was joint pain (40.0%), while the least common were burning sensation in the feet and visual disturbances (5.0 each). The level of medication adherence was mostly in the moderate category (96.0%). The results showed no relationship between the side effects of OAT use and medication adherence in tuberculosis patients, with a p-value of 0.521.